Nathaniel’s Ambition to Revenge on Simon Lovelace Discribed in Jonathan Stroud's The Bartimaeus Trilogy: The Amulet of Samarkand - Alfian Rheza Arjuna (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This thesis is entitled Nathaniel’s Ambition to Revenge on SimonLovelace Described in Jonathan Stroud’s The Bartimaeus Trilogy: The Amuletof Samarkand has an objective to analyze ambition and motive of Nathanielalias John Mandrake to revenge on Simon Lovelace as his enemy. Theresearcher used descriptive qualitative method to find out Ambition and motiveof Nathaniel alias John Mandrake after Humiliated by Simon Lovelace. Whilelibrary research method was used to gain any references dealing with the objectof analysis. Technique of analysis is divided into two, there are structural andpsychology approach. Structural approach was used to analyze structuralelements like general description, conflict, and setting, while psychologicalapproach was used to analyze and describe problems dealing with the object ofstudy. The collected data were analyzed by reading the novel. The researcherpresents all the data by the quotation through general description, conflict andsetting. The results of this research show that the main character is described asa person who is genius, clever, restless, arrogant, and curious. He belongs toround dynamic character since he has more than one specific traits and he alsochanges from the beginning till the end of the story. The main character alsoexperiences internal conflict about him admitting the truth about who steal theamulet, to disobey his master, blame himself and also external conflict againsthis master, Bartimaeus, Maurice Schyler, The Resistance and Simon Lovelace.The setting in this novel is divided into setting of place; Attic room, SirUnderwood house, Boarded-up building, Heddleham Hall, Small library andThe hall of Heddleham Hall, setting of time; morning in boarded-up building,10.15 am and setting of social on high social class. Nathaniel alias JohnMandrake's ambition is motivated by humiliation and murder drives him to gaineverything that needs to commit revenge. Living as magician which is alwayssurrounded by ambition and domination, losing someone that he loves,humiliated and be degraded by other.Keywords: Ambition, Amulet of Samarkand, Jonathan Stroud, Motive, Revenge